1993
DOI: 10.2169/internalmedicine.32.565
|View full text |Cite
|
Sign up to set email alerts
|

Integrin VLA-5 Negative Primary Plasma Cell Leukemia.

Abstract: Wepresent a case of primary plasma cell leukemia with Bence Jones proteinuria. After combination chemotherapy, leukemic cells and the urinary levels Bence Jones protein were decreased. Small lytic bone lesions were detected only in the skull. Typical plasma cells were rarely seen in peripheral blood on the hyperleukocytic phase, however they were increased in the advanced stages. The most important diagnostic sign was persistent expression of CD38antigen on leukemic cells throughout the entire course of the il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…42 Extramedullary MM or PCL is also associated with loss of very late antigen-5 (VLA-5), 39,43 LFA-3, 37,44 and tetraspanin proteins, such as CD9 and CD82, which are cell surface molecules involved in adhesion, motility, and invasion. 6,45 Down-regulation of chemokine receptors, such as CXCR4 on tumor cells, may also lead to impaired retention of PCL in the BM.…”
Section: Adhesion Molecules and Chemokine Receptorsmentioning
confidence: 99%
“…42 Extramedullary MM or PCL is also associated with loss of very late antigen-5 (VLA-5), 39,43 LFA-3, 37,44 and tetraspanin proteins, such as CD9 and CD82, which are cell surface molecules involved in adhesion, motility, and invasion. 6,45 Down-regulation of chemokine receptors, such as CXCR4 on tumor cells, may also lead to impaired retention of PCL in the BM.…”
Section: Adhesion Molecules and Chemokine Receptorsmentioning
confidence: 99%
“…Opinions on the role of late activation antigens in PCL are divided. Some authors have observed the expression of all these molecules on leukemic cells, while others have found the presence of VLA-4 combined with an absence of VLA-5 expression and stated that this surface antigen constellation was important for leukemic proliferation [45,46]. The expression of VLA-4 on the leukemic cells is a requisite of their increased invasiveness because contact between this antigen and its ligand in a capillar wall leads into extravasation of those cells from the blood into extravascular space [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with a poor prognosis, with a mean survival of less than 8 months [47] and a 5-year survival of 13% [3]. PCL is frequently the initial presentation of a plasma cell dyscrasia [49][50][51][52][53] or it may occur many years into the disease [54][55][56]. Our patient had a few peripheral blood plasma cells on presentation, which disappeared with successful treatment of his myeloma, but terminally he had a leukemic picture, with progression from 4 to 28% (4,000/l) peripheral blood plasma cells over 9 days.…”
Section: Discussionmentioning
confidence: 99%